Surrogacy: freedom and autonomy for women to make decisions regarding their own body: An ethical and legal approach - Mota Rodríguez, Alicia; Ruíz Canizales, Raúl (DIXI, 2020)
Objectives: This article is an approach to the ethical and legal problems involved in surrogacy. It briefly analyzes the argument based on the freedom and autonomy that every legal subject possesses over their own body in States with a neoliberal political system.Methodology: Likewise, through an analysis, the role played by both freedom and autonomy to validate decision-making by the subjects in question, especially that concerning the surrogate woman, will be addressed.Findings: the findings report that it is often assumed that this assisted reproduction practice represents, in most cases, a commodification of the human body.Conclusions: the findings call into question the rights, freedoms and even the dignity of pregnant women who participate in this novel method of reproduction.
Keywords: ethics; morals and freedom; autonomy; commodification; surrogacy; motherhood; body and gestation